The United Nations General Assembly Resolution (UNGAR)1 As a Source of International Law: Toward a Reformulation of Sources of International Law - Kadir, M. Ya'kub A. (UI Scholars Hub, 2011)
The changes in international community since 1945 have led to fundamental disputes on the sources of international law, in particular, the notion of the United Nation General Assembly Resolution to be a source of international law in comparison to the traditional sources as stated in article 38(1) International Court of Justice Statute. The fact that the existed sources are not able to maximize the role of international law in maintaining peace and security in the world would be an essential trigger to have a preliminary discussion on the issue. This paper attempts to identify to what extend the possibility of UNGAR to be a source of international law in conformity with the principle of democracy and justice.